Redox‐Responsive Micelles with Cores Crosslinked via Click Chemistry. Issue 12 (6th May 2016) - Zhang, Xiaojin; Dong, Hui; Fu, Shuangli; Zhong, Zhenlin; Zhuo, Renxi
Abstract : Redox‐responsive micelles with cores crosslinked via click chemistry are developed to improve the stability of polymer micelles. Amphiphilic block copolymer mPEG‐ b ‐P(DTC‐ADTC) with pendant azido groups on the hydrophobic chains is synthesized by the ring‐opening polymerization of 2, 2‐bis(azidomethyl)trimethylene carbonate (ADTC) and 2, 2‐dimethyltrimethylene carbonate (DTC) with monomethoxy poly(ethylene glycol) (mPEG) as an initiator. mPEG‐ b ‐P(DTC‐ADTC) self‐assemble to form the micelles in aqueous solution and the cores of the micelles are crosslinked via click chemistry to afford redox‐responsive core‐crosslinked micelles. Core‐crosslinking enhances the stability of the micelles in aqueous solution and improve the drug‐loading property. The redox‐responsive core‐crosslinked micelles can be reduced by the addition of reducing agents such as dithiothreitol (DTT), and thus release the loaded drug quickly in the presence of DTT. Abstract : Azide‐bearing poly(ethylene glycol)‐polycarbonate block copolymer (mPEG‐b‐P(DTC‐ADTC)) self‐assembles to form micelles in water. The micelle cores are crosslinked with a disulfide‐containing dialkynyl compound (SS‐Linker) via the azide‐alkyne click reaction to enhance the stability of the micelles and endow the micelles with redox‐responsive ability.